The Impact of Climate Change on Financial Markets and Sustainable Investment Strategies : Evidence from Finland - D C, Manisha (My University, 2026)
Climate change has transformed from an environmental concern to a systemic financial risk affecting asset prices, market stability, and capital allocation. In this thesis, it is investigated how climate-related factors influence financial markets and sustainable investment strategies in Finland. Specifically, it examines whether climate risks are priced into firms' valuations, how the performance of sustainable investment instruments is during climate-related market stress, and which factors drive firms' decisions to adopt green bond financing. The theoretical framework is based on climate risk pricing theory, carbon pricing mechanisms, and sustainable investment theory. Key concepts include transition risk, physical risk, carbon premium, greenium, and climate beta. A balanced panel dataset comprising annual observations from 10 publicly listed Finnish firms across sectors over the period 2010–2025 is used, yielding 160 firm-year observations. Panel regression with firm and year fixed effects is employed to analyze the relationship between climate-related variables, market capitalization, and volatility, while logistic regression is applied to examine the determinants of green bond issuance. The results indicate that climate-related policies are associated with financial market outcomes. Periods characterized by major policy developments such as the Paris Agreement, Finland’s carbon neutrality target, and the EU Climate Law are found to be associated with lower firm valuations and higher market volatility. Carbon pricing is identified as a significant factor in green bond issuance, as increasing prices in the EU Emissions Trading System are linked to higher levels of sustainable financing activity. Firm size is also found to be positively associated with the likelihood of issuing green bonds, suggesting that larger firms may have greater access to financial resources and face higher regulatory pressure. Evidence consistent with the greenium phenomenon is observed, suggesting that investors may accept slightly lower risk-adjusted returns in exchange for environmental benefits and perceived safety. These findings provide evidence supporting the growing importance of climate risks in financial decision-making. The study contributes to the literature regarding climate finance by providing evidence based on data from a small, advanced economy with strong regulations and ambitious targets. For investors, it is suggested that value may be found in incorporating climate risk analysis into portfolio management. For corporate managers, the results indicate that environmental practices may be rewarded through long-term stock price appreciation.
Keywords: risks; emission trade; greenhouse gases; investments; environmental responsibility; climate changes; financial markets; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance